Welche Konzeption der Sprache für die Giottodidaktik? - SKOWRONEK, Barbara (Uniwersytet im. Adama Mickiewicza, 1996)
In this article, glottodidactics is presented as an independent, empirical, interdisciplinary and humanistic scientific discipline, which is engaged in the teaching and learning of foreign languages. The goal of this article is to approach a justification by glottodidactic facts of social theories of language communication competence (Zgółka 1980) as well as the social theory of language acquisition competence (Wł. Zabrocki 1990).